Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario) - Benoît, Josée; Dagnogo, Djenaba Sarah; Renaud, Alexandre (2023)

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Insertion professionnelle dans le domaine de la santé des personnes immigrantes francophones vivant en situation minoritaire - Forest, Mariève; Goss Gilroy Inc (Ministère Immigration, Réfugiés et Citoyenneté Canada, 2020)

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

Rapport provincial sur les SSEF (données de 2018-2019) - Réseau des services de santé en français de l'Est de l'Ontario; Institut Ozi (2020)
Le projet OZi a pour objectif de colliger et d’analyser des données afin de dresser un portrait de la capacité de SSEF. Cette initiative cherche à pallier le manque de données normalisées afin de permettre une planification efficace et une prise des décisions éclairée. Grâce au portail OZi, les fournisseurs de services de santé (FSS) financés par les RLISS ont fourni des données de référence sur leur capacité en matière de SSEF. Le présent rapport porte sur la deuxième année de collecte de données (année 2018-2019). L’analyse porte sur quatre perspectives : la répartition des FSS, le continuum des services, la conformité en matière de désignation et les ressources humaines.

Contributions d’OZi à l’état des lieux des services de santé en français en Ontario. - Scullion, David; Taillon, Myriam; Ranger, Marie-Christine; Glaude, Normand; Desaulniers, Jacinthe (Minorités linguistiques et société, 2024)
Entre 2017 et 2020, l’organisme OZi a effectué la collecte et l’analyse de données sur les services de santé en français à l’échelle de la province, dans le cadre de la Loi sur les services en français de l’Ontario. Les résultats de cette recherche descriptive et exploratoire portent sur la répartition géographique de l’offre des services de santé en français, le continuum de soins, les exigences de la désignation et les ressources humaines possédant des capacités linguistiques en français. Ces résultats permettent de dresser l’état des lieux des services de santé en français en Ontario, en mettant en lumière les points forts comme les lacunes des services de santé en français. Les résultats sont discutés sous l’angle de l’accès et la planification des services de santé en français ainsi que celui de la performance de la désignation. Mots-clés : santé, offre active, Ontario, désignation des fournisseurs de santé, continuum de soins

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services